Impacto de la renta de recursos naturales en la diversificación de productos exportables: un análisis con datos panel para 100 países, periodo 1995-2018. - Torres Martínez, Maritza del Carmen (2022)
Export losses during the COVID pandemic in 2020 were -1.2% in developed economies, while in Africa and Latin America it was -20.3% and 9.7% respectively, coincidentally these two regions have the highest rates of export concentration and are exporters of raw materials. Based on this, this research aims to determine the impact of natural resource incomes on the diversification of exports globally and by levels of dependence on natural resources in the period 1995-2018. The data were obtained from the Databases of the World Bank (2020) and UNCTAD (2019a). A GLS model was used to correct problems of autocorrelation and heteroscedasticity, in addition to second generation tests in the presence of transverse dependence, the Westerlund test (2007), the Fully Modified Ordinary Least Squares (FMOLS) and later the Granger causality. The GLS results show that there is a positive relationship between the two variables of the model, being statistically significant at the global level as for the levels of dependence. In the same way, Westerlund's cointegration test (2007) determined that there is a long-term equilibrium. In addition, it was determined that there is a bidirectional relationship between the concentration index and the income of resources. Among other policies to achieve diversification, it is recommended to strengthen the position of SMEs in international trade through reforms in the financial sector, so that they can access credit on better terms. Keywords: economic diversification, natural resources, Herfindahl-Hirschman, cointegration. JEL Classification C23 F15 O13